Evaluasi Program Makanan Bergizi Gratis (MBG) DI SD Negeri 1 Sukadanaham - Marsha Khanisa Lubis; Muhammad Fajar Dismawan; Sekar Putri Hapsari; Undang Rosidin; Handoko Handoko (Universitas Sebelas Maret, 2025)
This study evaluates the implementation of the Free Nutritious Meal Program (MBG) at SD Negeri 1 Sukadanaham using a mixed-methods approach. The research focuses on how the program affects student nutrition, learning outcomes, and overall school-level management. The findings indicate that the MBG program has a positive impact on students' learning readiness, concentration, and motivation. Students who participate in the program demonstrate higher attendance rates and better engagement during lessons. However, the study identifies several operational challenges, including limited menu variety, inefficient food distribution timing, and the unintended social impact on local school canteen vendors. In conclusion, while the program is a vital instrument for improving student health and educational quality, its success depends on sustainable management and contextual integration. The study recommends improving implementation strategies, enhancing stakeholder involvement, and tightening supervision of food quality and variety. By addressing these management gaps, the MBG program can more effectively achieve its goal of supporting the holistic development of elementary school students.Keywords: Free Nutritious Meals Program, CIPP Evaluation, Elementary School